Crystalline H-aggregate nanoparticles for detecting dopamine release from M17 human neuroblastoma cells. Issue 39 (13th September 2022) - Reddy, Nitin Ramesh; Dicce, Arianna; Ma, Yiping; Chen, Li-Mei; Chai, Karl X.; Fang, Jiyu
Abstract : Crystalline H-aggregate nanoparticles of a cyanine dye were developed as a highly efficient photo-induced electron transfer probe for the detection of dopamine, which shows that the dopamine release from cells was enhanced by nicotine stimulation. Abstract : Dopamine (DA) is an important neurotransmitter, which is essential for transmitting signals in neuronal communications. The deficiency of DA release from neurons is implicated in neurological disorders. There has been great interest in developing new optical probes for monitoring the release behavior of DA from neurons. H-aggregates of organic dyes represent an ordered supramolecular structure with delocalized excitons. In this paper, we use the self-assembly of 3, 3′-diethylthiadicarbocyanine iodide (DiSC2 (5)) in ammonia solution to develop crystalline H-aggregate nanoparticles, in which DiSC2 (5) molecules show long-range π–π stacking. The crystalline H-aggregate nanoparticles are stable in cell culture medium and can serve as an efficient photo-induced electron transfer (PET) probe for the detection of DA with the concentration as low as 0.1 nM in cell culture medium. Furthermore, the crystalline H-aggregate nanoparticle-based PET probe is used to detect the release behavior of DA from the M17 human neuroblastoma cells. We find that the DA release from the cells is enhanced by nicotine stimulations. Our results highlight the potential of crystalline H-aggregate nanoparticle-based PET probes for diagnosing nervous system diseases and verifying therapies.